ВПЛИВ СТАТИСТИЧНОГО ХАРАКТЕРУ ПАРАМЕТРІВ ЕЛЕМЕНТІВ СИСТЕМИ НА РІВЕНЬ ЗАРЯДУ НАКОПИЧУВАЧА - Осипенко, К.С.; Жуйков, В.Я. (Інститут електродинаміки НАН України, Київ, 2019)
A simplified equivalent block diagram of a system with a wind generator is presented. It is noted that in order to fulfill the maximum energy selection condition, it is necessary to determine the value of the storage charge current, the minimum charge energy and the maximum capacitance value, which depend on the statistical characteristics of theenergy at the output of the wind generator and the load. Equations for calculating these characteristics are given. It is shown that the connection of an additional storage, which provides a deterministic change of the load energy value, makes it possible to reduce the capacity of the main storage. References 8, table 1, figures 2.